A review on poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] and genetic modifications that affect its production - Tang, Hui Jia; Neoh, Soon Zher; Sudesh, Kumar (Frontiers in Bioengineering and Biotechnology, 2022)
Polyhydroxyalkanoates (PHAs) have garnered global attention to replace petroleum-based plastics in certain applications due to their biodegradability and sustainability. Among the different types of PHAs, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] copolymer has similar properties to commodity plastics making them a suitable candidate to replace certain types of single-use plastics, medical devices, and packaging materials. The degradation rate of P(3HB-co-3HHx) is faster than the commercial petroleum-based plastics which take a very long time to be degraded, causing harmful pollution to both land and marine ecosystem. The biodegradability of the P(3HB-co-3HHx) is also dependent on its 3HHx molar composition which, in turn influences the crystallinity of the material. Various metabolic pathways like the common PHA biosynthesis pathway which involves phaA, phaB, and phaC, β-oxidation, and fatty acids de novo synthesis are used by bacteria to produce PHA from different carbon sources like fatty acids and sugars respectively. There are various factors affecting the 3HHx molar composition of P(3HB-co-3HHx) like PhaCs, engineering of PhaCs, and the metabolic engineering of strains. It is crucial to control the 3HHx molar composition in the P(3HB-co-3HHx) as it will affect its properties and eventually affect its applications in different fields.